HIDROLISIS HASIL DELIGNIFIKASI TANDAN KOSONG KELAPA SAWIT DALAM SISTEM CAIRAN IONIK CHOLINE CHLORIDE - Gendish Yoricya, Shinta Aisyah Putri Dalimunthe, Renita Manurung, Nimpan Bangun (Universitas Sumatera Utara, 2016)
Palm Empty Fruit Bunches (TKKS) was the waste which has a fairly high content of lignocelluloses. Meanwhile, TKKS has not been utilize optimally. With a cellulose content of 45%-50%, TKKS then potentially be used as raw material for bioethanol. In the process of production bioethanol, delignification of lignocellulose the first phase was conducted to dissolve ligament between cellulose, hemicellulose and lignin. In this research, delignification process was carried out using NaOH in the ionic liquid system and without ionic liquids. The purpose of this research was to find out the highest content of cellulose which contained in the TKKS and to determine the hydrolysis of delignification results on palm empty fruit bunches and the best hydrolysis conditions was obtained at the hydrolysis process in the choline chloride ionic liquid system. Delignification process were performed using ionic liquids choline chloride (ChCl) in variety of cooking time with amount different ChCl. This research used TKKS powder cooked at a temperature 130 °C with a variety of cooking time 30, 60, and 90 minutes and the variation of ChCl 10%, 15% and 20% weight of TKKS. Delignification research results used ChCl obtained highest content of cellulose was 40,33%, hemicellulose 20,28%, and lignin 3,62% in cooking treatment 90 minutes and 15% ChCl. While delignification without ChCl obtained highest content of cellulose is 24,98%, hemicellulose 8,25%, and lignin 18,99% in cooking treatment 90 minutes. Delignification process using ChCl be able increase the degree of delignification as big as 61,45%. In the hydrolisis process, the main raw material used cellulose of delignification TKKS result, choline chloride, sulfatl acid, and distilled water. The hydrolysis stage in this research was carried out at temperature 105 0C, catalyst (H2SO4) 10% (w / w) cellulose, ChCl 10%, 15%, and 20% (w / w) cellulose and it was stirred at constant speed 120 rpm with reaction time of 30, 60 and 90 minutes. The result in the hydrolysis stage using ionic liquid obtained glucose. LUFF method analysis showed the maximum result of glucose 37.96% with the best conditions in reaction time 90 minutes and the amount of choline chloride 20%.